2011
DOI: 10.5194/nhess-11-1281-2011
|View full text |Cite
|
Sign up to set email alerts
|

An improved RST approach for timely alert and Near Real Time monitoring of oil spill disasters by using AVHRR data

Abstract: Abstract. Information acquired and provided in Near RealTime is fundamental in contributing to reduce the impact of different sea pollution sources on the maritime environment. Optical data acquired by sensors aboard meteorological satellites, thanks to their high temporal resolution as well as to their delivery policy, can be profitably used for a Near Real Time sea monitoring, provided that accurate and reliable methodologies for analysis and investigation are designed, implemented and fully assessed.In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…As for the comparison between WG refined fuels data and MODIS satellite products, the RST-OIL approach (Casciello et al, 2007, 2011, Grimaldi et al, 2009a, 2009b, 2011a, 2011b was applied. Results showed that no intense oil spills were observed in either the WG data or the satellite observations.…”
Section: Sea Water Optical Propertiesmentioning
confidence: 99%
“…As for the comparison between WG refined fuels data and MODIS satellite products, the RST-OIL approach (Casciello et al, 2007, 2011, Grimaldi et al, 2009a, 2009b, 2011a, 2011b was applied. Results showed that no intense oil spills were observed in either the WG data or the satellite observations.…”
Section: Sea Water Optical Propertiesmentioning
confidence: 99%
“…It is based on the use of historical series of satellite data for a complete signal characterization (spectral, spatial and temporal) followed by an anomaly detection step using automatically-generated local (i.e., for a specific time and place of observation) thresholds. In its application to oil spill detection, namely RST-OIL, TIR data acquired by AVHRR or MODIS have been used to detect different oil spills occurred in different areas in the past [20,26,27]. In this paper, we use MODIS 250 m spatial resolution optical data for the detection and the monitoring of oil spills.…”
Section: Methodsmentioning
confidence: 99%
“…Among the methodologies working in the optical band, the one specifically applied to oil detection based on the general robust satellite technique (RST), named RST-OIL [20,26,27], has already been successfully applied to Advanced Very High Resolution Radiometer (AVHRR) and Moderate Resolution Imaging Spectroradiometer (MODIS) TIR data [20,27], showing excellent performances with a high level of reliability (no false alarm). In this work, the same approach has been extended to MODIS visible bands to exploit their higher spatial resolution (250 m) than the thermal channel (1 km) to improve the detection sensitivity towards small spills such as in the wakes of ships or illicit vessel discharge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of these events shows that even the largest and seemingly well-prepared facilities can be vulnerable to Natechs if risks are not considered adequately. Grimaldi et al (2011) show the application results of an improved version of RST (Robust Satellite Technique) to maritime oil spill detection and monitoring. The proposed approach has been applied to the case of oil spills off the Kuwait and Saudi Arabian coasts in January 1991 and during the Lebanon War in July 2006.…”
mentioning
confidence: 99%